An Intelligent Sensor Based System for Real Time Heart Rate Monitoring (HRM) - Farin, Nusrat J.; Sharif, S. M. A.; Mobin, Iftekharul (Scientific Research Publishing, 2016)
A method and apparatus for monitoring heart rate of the heart using a wearable system is designed and implemented in this paper. A heart rate receives from heart beat signals and stores the data to a database and after a time period this method can determine an idle heart rate of the monitoring body. This idle heart rate is compared with the stored data and can determine the normal and abnormal heart rate variability. After the certain time period this system can detect the heart rate and also can send a signal to the user in time of abnormalities. Consequent estimations of heart rate variability are contrasted with this.
Keywords: Heart Rate; Micro-Controller; Heart Rate Monitor (HRM); Wearable System; Sensor Based System (SBS)